Kepemimpinan Kepala Desa Dalam Perencanaan Pembangunan Desa Watutau Kecamatan Lore Peore - Lisda Prisilia Tandiborong; Henry A Ruagadi; Arifin Balingki (Interdisciplinary Journal (IDe), 2023)
This research was motivated by the development development in Watutau Village, Lore Peore District, which was considered not running efficiently or had not run properly, marked by inadequate facilities and infrastructure for agriculture and village road infrastructure that was quite concerning, which made researchers interested in discussing the problem with the title "Village Head Leadership in Watutau Village Development Planning, Lore Peore District". The theories used in this study are leadership theory and development planning theory using qualitative descriptive approach methods and data collection techniques carried out by observation, interviews and documentation. From the results of the study, it was found that the leadership of the village head in development planning in Watutau village, Lore Peore sub-district was not democratic, and the factor that influenced the leadership of the village head in development planning was the lack of human resources. The village government does not understand the socio-cultural conditions of the community. Thus, the author advises the government, in this case, the village head as a leader in Watutau Village to be democratic in accepting and listening to the aspirations of the community, being transparent about development planning and being able to manage the natural resources owned by Watutau Village to develop the economic growth of the village community.